Profile of pharmaceutical recommendations in a criticalpatient unit of a hospital specializing in trauma in Fortaleza/CE - Erikson Pereira Gomes, Francisco; Bastos Luz, Patrícia; Mota Marques, Larisse; Morais e Silva, Renan (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: To characterize the profile of pharmaceutical recommendations (PR), phar-macotherapy problems encountered, and the patient population evaluated to illustrate the critical role of clinical pharmacists in emergency settings. Methods: Cross-sectional, descriptive and quantitative study of the profile of PR, carried out in a critical patient unit of a tertiary hospital specialized in trauma, located in Fortaleza-CE, between January and December 2022. PR and pharmacotherapy problems were classified according to the in-ternal criteria of the service itself. Descriptive statistics were performed, with calculations of absolute and relative frequencies, in addition to the mean and standard deviation of the variables studied. Results: We performed 797 PR involving 301 patients, with 66.42 PR per month on average. According to the ATC/WHO, the drugs most involved in PR acted on the digestive tract and metabolism (24.71%, n=197) and the nervous system (23.58%, n=188). The most prevalent problems in pharmacotherapy were: untreated health problem (36.51%, n=291) and unnecessary prescribed medication (12.42%, n=99). The most prevalent PR were: inclusion of medication (28.60%, n=228) and discontinuation of medication (13.55%, n=108). Acceptance of 82.70% of the recom-mendations was observed (n=659). Conclusions: This acceptance rate, achieved even during the first year of a clinical pharmacist’s integration into the unit, highlights the vital role of this professional in emergency and urgent care settings, enhancing patient safety and optimizing pharmacotherapy outcomes.